Influencing Factors of Net Interest Margin in Turkish Banking Sector - Serhat Yuksel; Sinemis Zengin (International Journal of Economics and Financial Issues, 2017)
The aim of this paper is to define the influencing factors of net interest margin in Turkish banking sector. Within this scope, the effects of 14 explanatory variables on net interest margin were analyzed. Moreover, quarterly data for the period between 2003 and 2014 was used in this study. After that, we created a model by using MARS method so as to illustrate the relationship. The major finding in this study is that net interest margin is negatively related with non-interest income, non-performing loans, total assets and exchange rates. According to these results, it was determined that banks should focus on the quality of the assets in order to increase net interest margin. In addition to this situation, volatility in exchange rates should also be taken into the consideration by the banks for this situation.